Sustainable Forests, Divided Power: Navigating the Complexities of Customary Forest Resource of Management in Aceh Jaya - Latif, Ikhwan Rahmatika; Hajad, Vellayati; Handayani, Sri Wahyu; Sudarman, Sudarman; Aziz, Chairul Iqbal (Department of Government Studies, Universitas Syiah Kuala, 2024)
Ensuring the sustainable development of forest resources is a crucial priority in different regions worldwide. This article seeks to clarify the interplay between conflict and collaboration in the management of forest resources in Aceh Jaya, a region characterized by complex socio-political dynamics. This study utilizes a qualitative research methodology, specifically employing a case study approach, to investigate and address research inquiries. The current research centers on the conflicts and collaboration that arise in forest management, with a specific focus on the involvement of traditional (customary) authorities and state governments. The study also aims to identify the main factors that impact their collaborative endeavors in the pursuit of sustainable forest practices. The study's findings offer valuable insights and recommendations that governmental bodies, traditional authorities, and other relevant stakeholders can use effectively to develop policies and practices for managing forest resources in this region.